2021
DOI: 10.21608/ejfsat.2021.49489.1177
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Self Poisoning and Its Relation With Personality Traits Among Admitted Cases to Menoufia Poisoning Control Center.

Abstract: Introduction: Suicide has been ranked among the top ten major causes of death worldwide. Self-poisoning throughout all ages is listed as one of the principal causes of unnatural deaths. Aim: Analysis of the pattern of suicidal self-poisoning cases with emphasis on its relationship with personality traits among admitted cases to Menoufia Poisoning Control Center (MPCC). Method: This was a cross-sectional, prospective study conducted on 1069 cases of suicidal self-poisoned cases attended to MPCC in one year. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Globally, self-harm is ranked second among females and third among males [ 40 , 47 ]. A recent study in Egypt reported that two-thirds of suicide self-poisoning cases occurred among females [ 48 ]. In Australia, the number of females attempting suicide by self-poisoning was greater than that of males (3:1) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Globally, self-harm is ranked second among females and third among males [ 40 , 47 ]. A recent study in Egypt reported that two-thirds of suicide self-poisoning cases occurred among females [ 48 ]. In Australia, the number of females attempting suicide by self-poisoning was greater than that of males (3:1) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the number of females attempting suicide by self-poisoning was greater than that of males (3:1) [ 24 ]. Females tend to consume items already available in the home, while males tend to ingest or purchase an item kept outside [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Females are more vulnerable to aggression and stress in most underdeveloped countries [26]. Women's suicidal behavior is in uenced by limited customs, lack of education, job opportunities, and the added weight of being a spinster [27]. COVID-19 lockdowns appear to have created a perfect setting for a rise in violence against women.…”
Section: Discussionmentioning
confidence: 99%